Correlation Between Homogeneity of Different Composite Resins and Their Adhesion to Glass Fiber Posts: In Vitro Assessment - Živilė Oleinikaitė; Gediminas Skirbutis; Greta Rutkauskaitė (Dentistry Journal)
Background and Objectives: This in vitro trial aimed to investigate if there is a correlation between the homogeneities of different composite materials and their adhesion to glass fiber posts (GFPs). Materials and Methods: Twenty intact human upper jaw central incisors extracted due to periodontal diseases were selected for this trial. Endodontic treatment was performed according to ISO recommendations. A total of 4 mm of guttapercha was left in the apical region. Canals were prepared for post insertion. Teeth were randomly allocated into the two following groups depending on the core restorative material (n = 10): I—cores build up with light cured composite; II—cores build up with dual cured composite resin. GFPs were inserted and cores were rebuilt with different composite resins. Longitudinal cuts were made across the axis of the teeth and examined under a scanning electron microscope (SEM). Statistical analysis was accomplished using Mann–Whitney U and Spearman tests (p < 0.05). Results: In the group where the number and size of pores at the interface of GFPs were analyzed, pores were found only in the specimens restored with the light-cured “bulk-filled” composite. In the group where the number and size of pores in the core material were analyzed, pores were found in specimens restored with both the light-cured “bulk-filled” composite and dual-cured resin composite. However, the dual-cured resin composite yielded better results in terms of core integration. Conclusions: There is no statistically significant correlation between the homogeneities of different composite materials and their adhesion to GFP.